TPACK and EdTech Integration in Teaching and Learning Process: A Systematic Literature Review (2014-2024) - Wang, Lixia; Lee, Jun Choi (Communications on Applied Nonlinear Analysis, 2024)
This systematic literature review aims to identify the relationship between Technological Pedagogical Content Knowledge (TPACK) and the integration of Educational Technology (EdTech) for facilitating teaching and learning. A search of the SCOPUS and Web of Science databases yielded 1711 and 18 articles, respectively. Following PRISMA 2020 guidelines, 151 studies published between 2014 and 2024 were included in the final analysis. Five major driving factors underpinning EdTech integration were identified: the relationship between TPACK and EdTech integration, the impact of teacher experience and professional development, the role of contextual factors, emerging trends in EdTech integration, and limitations and future research directions. The review found that teacher TPACK proficiency is strongly related to effective EdTech integration, enhancing student engagement, motivation, and learning outcomes. However, the effectiveness of EdTech integration is significantly influenced by contextual factors such as teacher experience, access to technology, school policies, and learner needs. The rise of mobile learning, artificial intelligence, and the COVID-19 pandemic has also impacted the overall landscape of EdTech integration, presenting both opportunities and challenges. The review emphasizes the need for more robust tools and methods to operationalize TPACK, a better understanding of technology leadership, and strategies to address the digital divide. It provides a nuanced understanding of the complex relationship between TPACK and EdTech integration, offering valuable insights for policymakers, educators, and researchers aiming to optimize technology-enhanced learning experiences. Keywords: TPACK, EdTech Integration, Systematic Literature Review, Educational Technology Tools, Teaching and Learning Process.